Among patients with laboratory‐confirmed influenza, does treatment with oseltamivir reduce morbidity and mortality?. Issue 1 (January 2017) - Attia, Maximos; John, Tobin; Dhanoya, Indeep; Shah, Syed
Abstract : EVIDENCE‐BASED ANSWER : Yes, in the hospital. Treatment with neuraminidase inhibitors (NAI), most commonly oseltamivir, is associated with improved survival in hospitalized patients. Survival is higher when NAI treatment is started within 5 days of illness (SOR: B, retrospective cohort). For outpatient adults, oseltamivir reduces the duration of symptoms with uncomplicated influenza by about 1 day, even when treatment is started 48 hours or more after illness onset. Oseltamivir reduces the risk of lower respiratory tract complications and admittance to hospital (SOR: A, meta‐analysis of RCTs).